Guide to project management strategies for complex projects - Shane, Jennifer Sue; Strong, Kelly C.; Gransberg, Douglas D.; Jeong, Hyung Seok (SHRP 2 report., 2015)
TRB's second Strategic Highway Research Program (SHRP 2) Report S2-R10-RW-2: Guide to Project Management Strategies for Complex Projects facilitates the application of a five-dimensional management approach for complex projects. The objective of the guide is to identify and communicate the critical factors involved in successfully managing complex transportation design and construction projects. A training course based on the information in the guide was also developed.